2019
DOI: 10.1111/joim.12956
|View full text |Cite
|
Sign up to set email alerts
|

The changing epidemiology of community‐acquired pneumonia: nationwide register‐based study in Sweden

Abstract: Background There is limited evidence on the impact of pneumococcal conjugate vaccine childhood immunization programmes (PCV‐CIP) on community‐acquired pneumonia (CAP) in individuals with underlying diseases. Methods A nationwide cohort study using Swedish health registers to assess the incidence of hospitalization with all‐cause (AC‐CAP) and pneumococcal or lobar (PL‐CAP) CAP between 2005 and 2015, in relation to PCV‐CIP introduction in 2007–09. Results In total, 303 691 episodes of AC‐CAP occurred, of which 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 31 publications
7
32
0
Order By: Relevance
“…In such patients an initial or follow up treatment using penicillins with or without β-lactamase inhibitors, macrolides, or 2nd generation cephalosporins may be inadequate. Fluoroquinolones, and more speci cally the so called "respiratory" uoroquinolones, provide excellent coverage according to our data and those of previous studies [19][20][21]. The use of uoroquinolones, however, has several important drawbacks for patients with signi cant comorbidities.…”
Section: Discussionsupporting
confidence: 67%
“…In such patients an initial or follow up treatment using penicillins with or without β-lactamase inhibitors, macrolides, or 2nd generation cephalosporins may be inadequate. Fluoroquinolones, and more speci cally the so called "respiratory" uoroquinolones, provide excellent coverage according to our data and those of previous studies [19][20][21]. The use of uoroquinolones, however, has several important drawbacks for patients with signi cant comorbidities.…”
Section: Discussionsupporting
confidence: 67%
“…In such patients an initial or follow up treatment using penicillins with or without β-lactamase inhibitors, macrolides, or 2 nd generation cephalosporins may be inadequate. Fluoroquinolones, and more speci cally the so called "respiratory" uoroquinolones, provide excellent coverage according to our data and those of previous studies [19][20][21]. The use of uoroquinolones, however, has several important drawbacks for patients with signi cant comorbidities.…”
Section: Discussionsupporting
confidence: 67%
“…Naucler et al investigated the changing epidemiology of CAP in Sweden by using a nationwide registry system. 19 They showed that the incidences of CAP decreased significantly by 36%, 20%, and 16%, respectively for ages <2, 2-4, and 5-17 years, when the pre-PCV period (years 2005-2006) was compared with the post-PCV period (years 2014-2015). 19 Similar results have been observed in studies conducted in other European countries, including Italy, the Netherlands, Israel, and France.…”
Section: Discussionmentioning
confidence: 98%
“…19 They showed that the incidences of CAP decreased significantly by 36%, 20%, and 16%, respectively for ages <2, 2-4, and 5-17 years, when the pre-PCV period (years 2005-2006) was compared with the post-PCV period (years 2014-2015). 19 Similar results have been observed in studies conducted in other European countries, including Italy, the Netherlands, Israel, and France. [20][21][22][23][24] Our study is the second to evaluate long term (over at least 7 years) impact of PCV13 on CAP and CAP-related hospitalization.…”
Section: Discussionmentioning
confidence: 98%